PERFIL DE RESISTENCIA GENOTÍPICA Y FENOTÍPICA PRESENTE EN BACTERIAS AISLADAS A PARTIR DE FÓMITES EN ARMENIA, QUINDÍO-COLOMBIA PERÍODO JUNIO-JULIO 2019 - Delia Piedad Recalde-Reyes (Asociación Colombiana de Infectología, 2021)
Introduction: Antibiotic-resistance is a phenomenon by which bacteria manage to survive antimicrobial treatment; with incidence in intra and extra hospital environments such as: water sources, agricultural / livestock sector and fomites. Aim: To describe bacteria present in high circulation fomites in a central-western region of Colombia, with their phenotypic sensitivity profile and presence of genes beta-lactamases (TEM, OXA3 and SHV). Methodology: We isolate bacterial strains from banknotes, escalator handrails and ATM buttons. We evaluated its phenotypic sensitivity profile by minimal inhibitory concentration automated technique using Vitek 2® and presence of genes for beta-lactamases type TEM-full, OXA-3 and SHV-full by conventional PCR. Results: A total of 30 isolates were obtained; Acinetobacter baumannii complex, was the most common; banknotes were the form with the highest number of isolates and resistance. Of the total isolates, 53% carried at least one of the genes studied. Phenotypically, gram-negative bacteria were identified with resistance against: Imipinem, Piperacillin / Tazobactam, Colistin, Ceftazidime, Tigecycline and Ceftriaxone; Gram-positive bacteria with resistance to: Quinupristin / Dalfopristin, Minocycline, Tetracycline, Teicoplanin, Nitrofuratoin, Oxacillin, Clindamycin, Trimethropine-sulfamethoxazole, and Minocycline. Conclusion: Taking into account the circulation of strains with these resistances, it is important to educate the community to avoid the acquisition or spread of infections due to the inappropriate handling of this type of inanimate elements.